Toxic Effects of Trichloroethylene on Rat Neuroprogenitor Cells - Mohamed M. Salama; Mohamed M. Salama; Doaa A. El-Naggar; Rania H. Abdel-Rahman; Seham A. G. Elhak (Frontiers Media S.A., 2018)
Trichloroethylene (TCE) is a common volatile organic solvent which is considered as an ubiquitous environmental pollutant. It is claimed to be a developmental neurotoxicant. Our group evaluated previously its impact on three-dimensional neurospheres in vitro. The current work aims to investigate the neurotoxic effects of a lower concentration of TCE on the same system. To perform the experiment, neural progenitor cells were obtained from the brains of nine newborn rats. Afterward, these cells were cultured in both growth and differentiation media to get the neurospheres. Cell cultures were divided into two groups: group 1 (control), group 2 (exposed to 0.25 μM TCE). Neurospheres were photographed at different durations and assessment of the morphological changes such as proliferation and differentiation of neurospheres was done. In addition, cell viability, apoptosis, and necrosis were analyzed using flow cytometry to clarify the mechanism of involved cytotoxicity. The results revealed that TCE-treated neurospheres showed significantly decreased proliferation on days 7 and 14. These cells failed to show the neurogenic differentiation seen in the neurospheres of the control group. Furthermore, a highly significant decrease in viability and a significant increase in the number of apoptotic cells were observed in the treated cells in comparison to the control group. The present work confirmed that TCE, at very low doses relevant to daily life exposure in humans, caused neurotoxic effects in 3D neurosphere model through the affection of neural proliferation and differentiation as well as disturbance of cell viability and apoptosis.